FTIR and WAXD Study of Regenerated Silk Fibroin - Kamalha, Edwin; Zheng, Yuansheng; Zeng, Yongchun; Fredrick, Mutua N. (Advanced Materials Research, 2013)
In this study, regenerated Bombyx Mori (B. Mori ) silk fibroin from two aqueous solvents was analyzed for structural deviations. Results from Fourier transform infrared spectroscopy (FTIR) and Wide angle x-ray diffraction (WAXD) implied great alteration in the secondary structure, crystallinity and molecular weight due to the regeneration process.
Keywords: Silk Fibroin (SF); Bombyx mori; Regeneration; FTIR; WAXD; Structure